Effects of scour-hole dimensions on lateral behavior of piles in sands. (July 2019) - Lin, Yunjie; Lin, Cheng
Abstract: Scour is a process of soil erosion around foundations caused by currents and waves, which can severely compromise the performance of the foundations. The scour process forms a scour hole around the foundation. The existence of the scour hole has been considered by many design standards for pile foundations such as those from the US Federal Highway Administration (FHWA) and American Petroleum Institute (API). However, these standards recommend different procedures to evaluate lateral responses of piles subjected to local scour that forms three dimensions of scour hole. This paper presents a series of three-dimensional finite element (FE) parametric analyses to examine the feasibility of the standard methods (FHWA and API) as well as an analytical solution proposed by the authors through varying scour-hole dimensions, soil properties, and pile properties. The results showed that the analytical solution provided conservative results while the standard methods provided mixed results compared with the FE analyses. The loss of pile lateral capacity due to scour was more significant in dense sands than in loose sands (approximately 10% more). For a given relative scour depth, the increase in pile diameter increased the scour-induced loss of pile lateral capacity.